2020
DOI: 10.1055/s-0039-3400266
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition in Musculoskeletal Imaging Using Artificial Intelligence

Abstract: Artificial intelligence (AI) has the potential to affect every step of the radiology workflow, but the AI application that has received the most press in recent years is image interpretation, with numerous articles describing how AI can help detect and characterize abnormalities as well as monitor disease response. Many AI-based image interpretation tasks for musculoskeletal (MSK) pathologies have been studied, including the diagnosis of bone tumors, detection of osseous metastases, assessment of bone age, ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…All 38 articles addressed an application of ML or DL with imaging data of MSK malignancies. Three review articles were found and excluded from statistical analysis [ 8 , 14 , 25 ]. 75.7% (28) of the studies were conducted retrospectively, 8.1% (3) were conducted prospectively and 16.2% (6) did not clearly state the study design.…”
Section: Resultsmentioning
confidence: 99%
“…All 38 articles addressed an application of ML or DL with imaging data of MSK malignancies. Three review articles were found and excluded from statistical analysis [ 8 , 14 , 25 ]. 75.7% (28) of the studies were conducted retrospectively, 8.1% (3) were conducted prospectively and 16.2% (6) did not clearly state the study design.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical imaging of degenerative pathological features in disease processes yields invaluable information relevant to the diagnosis, management or development of therapeutic measures to treat such diseases. 261 AI and DML are particularly well suited to the evaluation of large data sets in clinical imaging. A deep convolutional neural network trained on a large, manually evaluated data set of 1599 patients and 7948 IVDs has been developed and outperforms human evaluations of MRI data.…”
Section: How Ai and Dml Have Im...mentioning
confidence: 99%
“…Clinical imaging of degenerative pathological features in disease processes yields invaluable information relevant to the diagnosis, management or development of therapeutic measures to treat such diseases 261 . AI and DML are particularly well suited to the evaluation of large data sets in clinical imaging.…”
Section: How Ai and Dml Have Improved Clinical Spinal Imagingmentioning
confidence: 99%
“…13 However, introducing deep learning-based techniques to the extensive quality ground-truth training datasets is essential for the development of accurate algorithms. 47,48 Also, ethical dilemmas should be taken into consideration. When dealing with systems that operate with enormous amounts of data, patients' privacy as well as human dignity may be jeopardized, unless meticulous safety mechanisms are implemented.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%